Teneurin Structures Are Composed of Ancient Bacterial Protein Domains - Jackson, Verity A.; Busby, Jason N.; Janssen, Bert J. C.; Lott, J. Shaun; Seiradake, Elena (Frontiers in Neuroscience, 2019)
Pioneering bioinformatic analysis using sequence data revealed that teneurins evolved from bacterial tyrosine-aspartate (YD)-repeat protein precursors. Here we discuss how structures of the C-terminal domain of teneurins, determined using X-ray crystallography and electron microscopy, support the earlier findings on the proteins’ ancestry. This chapter describes the structure of the teneurin scaffold with reference to a large family of teneurin-like proteins that are widespread in modern prokaryotes. The central scaffold of modern eukaryotic teneurins is decorated by additional domains typically found in bacteria, which are re-purposed in eukaryotes to generate highly multifunctional receptors. We discuss how alternative splicing contributed to further diversifying teneurin structure and thereby function. This chapter traces the evolution of teneurins from a structural point of view and presents the state-of-the-art of how teneurin function is encoded by its specific structural features.